Statistical approaches for assessing meat quality and heifer rumen histology based on dietary forage - Benito-Díaz, Alberto; Sarmiento-García, Ainhoa; García-García, Juan José; Vieira, Ceferina; Domínguez, Esperanza; Bodas Rodríguez, Raúl; Gómez-Gordo, Luis; Vicente-Galindo, Purificación (Frontiers in Veterinary Science, 2024)
Feeding local forages to ruminants is a promising strategy for enhancing metabolic processes, promoting sustainable farming, and improving product quality. However, studies comparing the effects of different forages on rumen histology and meat attributes of heifers are limited and variable. This study evaluated the benefits of incorporating local forages into heifer diets by comparing barley straw (BS) and oat hay (OH) on heifer attributes focusing on meat quality (MQ) and rumen status (RS). Sixteen crossbred (Charolais x Limousin) female heifers (7 months of age, 263 ± 10.50 kg) were randomly assigned to two dietary treatments (BS or OH) over 120 days. Heifers fed OH showed enhanced RS (P<0.05), characterized by improved intestinal epithelial integrity and a lower percentage of hyperpigmented cells, suggesting a potential reduction in inflammatory processes compared to BS, which may indicate a lower risk of metabolic diseases. Despite this, no significant differences (P>0.05) were found in animal performance, chemical composition, and technological properties of the meat between the dietary groups, while lower levels (P<0.05) of certain saturated fatty acids (C12:0, C15:0, and C22:0) were found in the meat from heifers fed OH. Principal component analysis (PCA) reduced the variables and demonstrated that all variables assessed can be condensed into four new variables explaining 75.06% of the variability. Moreover, biplot analysis reveals that the OH diet could be discriminated from BS. Our findings suggest that OH is a valuable fibre source, positively influencing certain heifer attributes, and supporting sustainable animal agriculture practices.